PENGARUH PENGGUNAAN MEDIA POSTER TERHADAP MOTIVASI BELAJAR DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN BIOLOGI KELAS XI MA NW SUKAMULIA - Ariandani, Nunung (Cocos Bio, 2025)
This study aims to analyze the effect of learning media in form of posters on students’ motivation and learning outcomes in biology subjects at MA NW Sukamulia. The study was conducted with a quasi-experimental design, involving two classes: experimental class XI A which used poster media and control class XI B which applied conventional methods. Data were collected through questionnaires and learning outcome tests. The results show that students’ learning motivation in the experimental class, with an average questionnaire score of 81.4 and a standard deviation of 3.82, is higher than the control class which obtained and average score of 68 with a standard deviation of 6.47. independent T-test showed T count 7.9970, greater than T table 2.0227, indication a significant increase in students’ learning motivation using poster media. In terms of learning outcomes, the average pre-test score of the experimental class is 35.25 with an increase in the post-test to 46, while the control class shows a pre-test score of 29.52 and a post-test of 32.14. independent T-test for learning outcomes revealed T count 2.3136, higher than T table 2.0210, indicating a significant increase in the learning outcomes of students in the experimental class. Overall, the use of poster media significantly increased students’ motivation and learning outcomes in the experimental class compared to the control class.